2002
DOI: 10.1189/jlb.71.4.625
|View full text |Cite
|
Sign up to set email alerts
|

Activation of macrophages by gliadin fragments: isolation and characterization of active peptide

Abstract: Celiac disease, induced by dietary gluten, is characterized by mucosal atrophy and local inflammation associated with cell infiltration and activation. Unlike other food proteins, gluten and its proteolytic fragments, besides inducing a specific immune response, were shown to activate components of innate immunity and cause, e.g., direct stimulation of TNF-α and IL-10 and a significant rise in NO production by peritoneal macrophages. The identity of the active fragments was established by separating the peptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(8 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It implies that, in patients with CD, this peptide somehow finds a way to bind and specifically activate the latter cells, likely via a receptor to be identified. Another recent study suggests that some gluten‐derived peptides might activate innate immunity, but in that study, the activation of macrophages was not specific to patients with CD (40). b) A second question concerns the changes in the homeostasis of IEL that lead to the emergence of lymphoid malignancies in some CD patients.…”
Section: Update On Clinical and Epidemiologic Datamentioning
confidence: 84%
“…It implies that, in patients with CD, this peptide somehow finds a way to bind and specifically activate the latter cells, likely via a receptor to be identified. Another recent study suggests that some gluten‐derived peptides might activate innate immunity, but in that study, the activation of macrophages was not specific to patients with CD (40). b) A second question concerns the changes in the homeostasis of IEL that lead to the emergence of lymphoid malignancies in some CD patients.…”
Section: Update On Clinical and Epidemiologic Datamentioning
confidence: 84%
“…In this regard, potential targets that can affect M2 polarization becomes an attractive area of reaching mucosal healing which is the ultimate treatment goal of this kind of disorders 18 . In celiac disease, gliadin peptides induce activation of macrophages toward a pro-inflammatory M1 phenotype [6][7][8][9][10] . In vitro models of gluten toxicity are of particular importance for the development of novel treatment options for CeD.…”
Section: Discussionmentioning
confidence: 99%
“…M1 and M2 phenotypes of macrophages can be converted into each other in response to microenvironmental stimuli 5 .There are numerous MQs in the lamina propria of the small intestine, with a dual role of maintaining tissue homeostasis and participating in the development of intestinal inflammation. According to the reports, gliadin peptides, which trigger immune reactions in celiac disease (CeD), induce the activation of macrophages toward a pro-inflammatory M1 phenotype [6][7][8][9][10] . In vitro studies with murine MQ and human monocytic cell lines have shown that gliadin triggers the production of TNF-α, IL-8, RANTES, IL-1β and significantly increases nitric oxide (NO) upon activation of toll-like receptors 2 and 4 (TLR2/TLR4) 9 .…”
mentioning
confidence: 99%
“…Furthermore, it has been reported that the presence of protein in the polysaccharides structure can induce an inflammatory response in tissues that may limit the biological utilization of the polysaccharides (Tučková et al, 2002). Figure 1 presents the scheme for purification of water-soluble polysaccharides.…”
Section: Purifi C Ati Onmentioning
confidence: 99%
“…The elimination of proteins from the structure of gums is important since it leads to improving their thickening ability (Burkus & Temelli, 1998). Furthermore, it has been reported that the presence of protein in the polysaccharides structure can induce an inflammatory response in tissues that may limit the biological utilization of the polysaccharides (Tučková et al., 2002). Figure 1 presents the scheme for purification of water‐soluble polysaccharides.…”
Section: Purificationmentioning
confidence: 99%